KEEFEKTIFAN KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS VII MTs DINIYAH PANDAI SIKEK - Yulianti Rasyid, Suci Wulandari, Ellya Ratna, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research is (1) to describe the effectiveness of the sentence in the text of exposition of class VII students of MTsS Diniyah Pandai Sikek in terms of accuracy of reasoning include (a) logical ideas and (b) unity of ideas, 2) describe the effectiveness of the sentences in the expositional text of the seventh grade students of MTsS Diniyah Pandai Sikek in terms of language accuracy including (a) grammar, (b) exact words, and (c) exact spelling. The method in this research is descriptive method. Sources of research data are 19 texts written by students. The research findings are 10 effective sentences and 155 ineffective sentences of 165 sentences examined.Â Kata kunci: kalimat efektif, teks eksposisiÂ Â